Effect of replacing milk proteins with wheat gluten and soybean products on digestibility of nutrients and growth performance in nursery pigs - Richert, B.T.; Morrill, J.L.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to evaluate the nutritional value of processed wheat gluten for early-weaned pigs. The first experiment involved 72 weanling pigs with an avg age of 20 d and avg wt of 9.2 lb. Six diets were fed to the pigs in individual metabolism cages. Protein sources were casein, flash-dried wheat gluten, spray-dried wheat gluten, two solubilized wheat glutens, and soybean meal. Response criteria were N digestibility, biological value, and N retention. Casein had greater N digestibility, biological value, and N retention than the other protein sources. The wheat gluten products had greater N digestibility than soybean meal. Modification of the wheat gluten, to increase its solubility, resulted in marked decreases in biological value and N retention. Experiment 2 was a nursery growth assay. A total of 180 pigs were used, with an avg age of 25 d and avg wt of 12.3 lb. The five pelleted diets fed from d 0 to 14 were: 1) a high nutrient density diet (HNDD) with 20% dried whey and 20% dried skim milk (DSM); 2) HNDD with the DSM replaced by flash-dried wheat gluten and lactose; 3) HNDD with the DSM replaced by spray-dried wheat gluten and lactose; 4) HNDD with the DSM replaced by solubilized-modified wheat gluten and lactose; 5) HNDD with DSM replaced by soy protein isolate and lactose. All pigs were fed a common diet from wk 3 to 5 of the experiment. No differences in ADG or ADFI were noted for d 0 to 14. Feed to gain was best for pigs fed diets with spray-dried wheat gluten and worst for those fed diets with soy-isolate. For d 0 to 35, pigs fed diets with flash-dried wheat gluten had lower ADG and ADFI than pigs fed diets with spray-dried and solubilized-modified wheat gluten. Furthermore, pigs fed spray-dried wheat gluten during Phase I had the greatest overall growth performance, with a 19% improvement in ADG compared to pigs fed DSM.
Keywords: Swine; Starter; Dried skim milk; Wheat; Gluten; Process; Digestion; Performance